ANALISIS STRATEGI KOMISI PEMILIHAN UMUM (KPU) DALAM UPAYA MENINGKATKAN PARTISIPASI MASYARAKAT KOTA SORONG - Ferdinandus, Arce Yulita; Muskita, Susana Magdalena; Pakpahan, Ratna Rosmauli (Fakultas Ilmu Sosial dan Ilmu Politik, 2024)
Regency General Election Commission's strategy so far has been to use a communication approach and has not yet made people understand who they are voting for and what the importance of using their right to vote is, considering that many people still put aside general elections, because they consider them to be less important to them. So the problem in the research is the General Election Commission's strategy in an effort to increase community participation in Regency? The type of approach used in this research is a qualitative approach. The research data used includes primary and secondary data obtained through interviews and document studies. Data was analyzed qualitatively. The location of the research was on Sorong City. The research results show that the strategy that needs to be carried out by the Sorong City KPU is an agenda setting strategy, which has 2 levels, namely; (1) The first level of agenda setting is an effort to develop general issues that are considered important. (2) The second level of agenda setting is determining the parts or aspects of the general issue that are considered important. So there is a need for a media agenda by socializing through the media to influence the public agenda.